5, 10-methylenetetrahydrofolate reductase gene mutation and reproductive outcome: how much do we know? A case series in Indian population - Singh, Pooja Nadkarni; Raghav, Mridula; Singh, Prabhkar; Viradiya, Vanita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Recurrent pregnancy loss (RPL) defined as loss of two or more pregnancies is one of the reasons why couples visit an ART clinic. 2-5% of RPL cases show an abnormal parental karyotype. Folic acid is an essential B vitamin involved in processes of fundamental importance for cell division and embryo development. Folic acid deficiency can have effect on many processes involved in oocyte development, acquisition of endometrial receptivity, embryo implantation and also in the maintenance of pregnancy. The 5, 10-methylenetetrahydrofolate reductase (MTHFR) enzyme plays an important role in folate metabolism. The most investigated MTHFR gene mutations are single nucleotide polymorphisms (SNPs) at the mRNA positions 677 (rs1801133) and 1298 (rs1801131). MTHFR gene mutations are found less in Asian population and hence have not been studied or evaluated much. We presented a case series of 3 different cases of MTHFR gene mutation variants that were managed at our ART center. Testing for MTHFR gene mutation after 3 early pregnancy failures/missed abortions, PGT-A and surrogacy being our proposed interventions.